FACTORS AFFECTING PROFITABILITY IN BASIC MATERIALS COMPANIES LISTED ON IDX - Aryanto, Reviena; Susanto, Liana (International Journal of Application on Economics and Business, 2025)
To determine what factors can influence profitability in basic materials companies listed on the IDX during 2019-2021, research was conducted using four independent variables such as, company size, company efficiency, leverage, and company age. Those independent variables are used to find out whether they are affecting company’s profitability. Company size is measured using the natural logarithm of total sales, company efficiency is measured using TATO (total asset turnover ratio), leverage is measured using DER (debt to equity ratio), company age is measured by subtracting the year of research from the year the company was listed on the IDX and profitability is measured using ROE (return on equity). The number of samples used in this research are 49 basic materials companies. The number of samples was processed and analyzed using a purposive sampling method. In processing the data, this research uses a multiple linear regression analysis and uses Statistical Program for Social Science (SPSS) 25 software. The result of the research shows that leverage has a significant and negative effect on profitability and company age does not have a significant effect on the profitability of basic materials companies listed on the IDX. Meanwhile, company size and company efficiency have a significant and positive effect on the profitability of basic materials companies listed on the IDX during 2019-2021.